Chitosan and Red Ginger Extract Patches for Diabetic Foot Ulcers: An Alternative for Urban Healthcare Challenges - Yovita Levania; Michael Michael; Eko Adi Prasetyanto (Jurnal Perkotaan, 2025)
Diabetic foot ulcers (DFUs) are a severe complication of diabetes, particularly in urban areas where healthcare access and infection risks pose significant challenges. This study investigates the potential of transdermal patches combining chitosan and red ginger (Zingiber officinale var. rubrum) extract to improve DFU care. Patches were formulated with varying concentrations of chitosan (2%, 3%, and 4%) and red ginger extract (0%, 5%, 10%, and 15%) and evaluated for physical properties, moisture retention, durability, and antimicrobial activity against Staphylococcus aureus. Results identified 3% chitosan with 5% red ginger extract as the optimal formulation, offering superior water retention, balanced durability, and moderate antimicrobial efficacy. These findings highlight the potential of chitosan-red ginger patches as cost-effective, adaptable solutions for DFU care, addressing critical needs for infection control, hydration, and patient comfort in resource-limited urban healthcare settings. Future studies should validate clinical efficacy and investigate scalability for broader implementation.